Investigating the past using remote sensing techniques - Themistocleous, Kyriacos; Anayiotos, Andreas (My University, 2021)
This study will document the abandoned Carmelite monastery located in Polemidia, Limassol District, Cyprus. The monastery was abandoned in 1570 and recently restored by the Greek Orthodox Church, with the name of Panagia Karmiotissa. The church of Panagia Karmiotissa is the only preserved Gothic church in the Limassol area during the time of the Frankish House of Lusignan in Cyprus. To the north area of the church there is a spring, where legend states that a holy shrine of the Virgin Mary springs miraculously. In between the Church and the spring, the rubble of a separate construct is visible, which may possibly be the monk residence halls. From the end of the 12th century to the 19th century, little is known about the site. This study investigates and documents both the church and the surrounding area, using remote sensing data, aerial images and ground penetrating radar. This investigation using remote sensing techniques is an effort to uncover and understand the history of the site.
Keywords: Remote Sensing; Cultural Heritage; Ecclesiastical monuments; Monasteries; Cyprus